The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3847/1538-4357/ab9084
|View full text |Cite
|
Sign up to set email alerts
|

Consistently Simulating a Wide Range of Atmospheric Scenarios for K2-18b with a Flexible Radiative Transfer Module

Abstract: The atmospheres of small, potentially rocky exoplanets are expected to cover a diverse range in composition and mass. Studying such objects therefore requires flexible and wide-ranging modeling capabilities. We present in this work the essential development steps that lead to our flexible radiative transfer module, REDFOX, and validate REDFOX for the solar system planets Earth, Venus, and Mars, as well as for steam atmospheres. REDFOX is a k-distribution model using the correlated-k approach with the random ov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 121 publications
1
68
0
Order By: Relevance
“…While our standard models, presented in Section 4, are statistically able to reproduce the observed spectrum of K2-18b, here we test some scenarios allowing for CH 4 VMR to be as small as retrieved by all the other teams who analysed the data so far. Indeed, our nominal model gives a CH 4 VMR of ≈ 5 +1 −2 % (for metallicities between 65 and 500 (Z/H) ), while Benneke et al (2019a), Madhusudhan et al (2020) and Scheucher et al (2020) give, respectively, a 2σ upper limit of 0.248%, a 99% upper limit of 3.47%, and an upper limit of 460 ppm. Benneke et al (2019b) propose three explanations to this depletion: (i) a high internal temperature, either from residual heat of formation or tidal heat-ing, (ii) a low C/O ratio resulting from planetary formation process, and (iii) a catalytic destruction of CH 4 by photolysis.…”
Section: Ch 4 -Depleted Scenarios For K2-18bmentioning
confidence: 79%
See 3 more Smart Citations
“…While our standard models, presented in Section 4, are statistically able to reproduce the observed spectrum of K2-18b, here we test some scenarios allowing for CH 4 VMR to be as small as retrieved by all the other teams who analysed the data so far. Indeed, our nominal model gives a CH 4 VMR of ≈ 5 +1 −2 % (for metallicities between 65 and 500 (Z/H) ), while Benneke et al (2019a), Madhusudhan et al (2020) and Scheucher et al (2020) give, respectively, a 2σ upper limit of 0.248%, a 99% upper limit of 3.47%, and an upper limit of 460 ppm. Benneke et al (2019b) propose three explanations to this depletion: (i) a high internal temperature, either from residual heat of formation or tidal heat-ing, (ii) a low C/O ratio resulting from planetary formation process, and (iii) a catalytic destruction of CH 4 by photolysis.…”
Section: Ch 4 -Depleted Scenarios For K2-18bmentioning
confidence: 79%
“…Using an interior model, Madhusudhan et al (2020) indicated that if the planet had a small rocky core and a thin H 2 /He atmosphere, an ocean of liquid H 2 O could exist. However, Scheucher et al (2020) ruled out this possibility, arguing that an H 2 O ocean would partially evaporate in the atmosphere, giving a spectrum that would be incompatible with the data. In the present work, we use Exo-REM, our self-consistent one-dimensional (1D) atmospheric model adapted for transiting exoplanets to study K2-18b atmospheric composition assuming a thick H 2 -He atmosphere.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…For the IR opacities, we took the Rosseland mean κ R for solar composition (Freedman et al 2008) as our baseline. In our opacity 1 setting, we adopted γ = 0.123 and κ IR = 1 × 〈κ R 〉 (bracket 〈〉 denotes average over wavelength) which was confirmed to reproduce well the p-T profiles published for the H 2 /He/H 2 O atmosphere of K2-18 (Scheucher et al 2020). As π Men cʼs atmosphere may also contain large abundances of CO 2 , our opacity 2 setting adopted γ = 0.500 and κ IR = 2 × 〈κ R 〉, which is appropriate for a CO 2 -dominated atmosphere with some admixture of H 2 /He.…”
Section: Appendix D Interior Structure Modelmentioning
confidence: 61%